Potentiometric Transducers for the Selective Recognition of Risperidone Based on Molecularly Imprinted Polymer - Najwa I. Abdulla; Hamsa M.Yaseen (College of Pharmacy University of Baghdad, 2017)
Graphite Coated Electrodes (GCE) based on molecularly imprinted polymers were fabricated for the selective potentiometric determination of Risperidone (Ris). The molecularly imprinted (MIP) and nonimprinted (NIP) polymers were synthesized by bulk polymerization using (Ris.) as a template, acrylic acid (AA) and acrylamide (AAm) as monomers, ethylene glycol dimethacrylate (EGDMA) as a cross-linker and benzoyl peroxide (BPO) as an initiator. The imprinted membranes and the non-imprinted membranes were prepared using dioctyl phthalate (DOP) and Dibutylphthalate (DBP) as plasticizers in PVC matrix. The membranes were coated on graphite electrodes. The MIP electrodes using (AA) and (AAm) showed a near nernstian and nernstian response with slopes of 55.2Â±0.1 and 59.0Â±0.2 mV/decade, correlation coefficient (r2) 0.9997 and 0.9999, a linear response for a concentration range of (1.0Ã-10-6 - 1.0Ã-10-2) M and (5.0x 10-7 to 1.0 x 10-2) M respectively. The response time of the prepared electrodes was less than 30 seconds. The electrode responses were stable in a pH range (4-8). The electrodes exhibited good selectivity over a wide range of interference. The most effective electrode (Ris-MIP GCE) was used to determine the concentration of (Ris.) in some pharmaceutical formulations. The electrodes could be successfully used within (7and13) weeks respectively without any drift. Keywords: Ion-selective electrodes, Molecularly imprinted polymer, PVC membrane coated graphite electrode, Risperidone.